EKSISTENSI BELAJAR FI AL QUR’AN DAN FI AL HADITS - Fikri Aulia Rahman; Yayat Suharyat (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
Al-Quran and Hadith are the main guideline for Muslim, altrough in islam there are qiyas , Istihsan and others. Al-Quran is the first foundation for mankind, unless after the argument is not found in the Al-Quran should use the Hadith. Then it is the relation to learning that is the process of changing behaviour or the process of developing knowledge for an individual. It makes learning is an obligation for every individual. The goal is to be able adapt in the future and develop self ability. The the relationship of the Al-Quran and Hadith to learning is empesized more in the process of trasfering knowledge between teachers and students or other wise with their environment, in order to make an individuals more devout their relagion and eminent in their knowledge.